The Impact of Management Control Systems on the Financial Performance of Companies in Light of Institutional Factors: An Empirical Study on a Sample of Non-Financial Companies Listed on the Iraqi and Kuwaiti Stock Exchanges - Hassan, Zain Al-Din Mohammed; Tamimi, Suhail Al (NIU Journal of Management Sciences, 2026)
This study aimed to demonstrate the impact of management control systems on the financial performance of companies, as well as the indirect impact of these systems on financial performance through institutional factors, specifically the legal framework. The research relied on a sample of non-financial companies in the financial markets of both Iraq and Kuwait. Information published in the annual financial statements of 14 non-financial companies was used for the period from 2020 to 2024. To achieve the study's objectives, a proposed model was developed and simulated using the R2 programming language and various statistical software programs. The results showed that the third proposed model was the best for measuring the variables after the simulation. Furthermore, the results demonstrated a direct and significant positive impact of planning budgets on the legal framework, while no positive or significant impact was found for performance reports. The legal framework also had no effect on the financial performance of companies in either country. In addition, the results showed no direct and significant impact of planning budgets and performance reports on the return on assets for either Iraqi or Kuwaiti companies. The mediation of institutional factors has not been achieved in Kuwaiti and Iraqi companies. Keywords: Management control systems, financial performance, and institutional factors.